Acceptability of the concept of shariah compliant procurement in the Malaysian construction industry - Hayder Ali, Faris; Che Haron, Roziha (2019)
Construction procurement is a process of acquiring a construction project and it is very crucial for the success of any projects. In the past and present, majority practice of procuring projects in Malaysia are involving interest, uncertainties, gambling and other prohibited matters. Therefore, the concept of Shariah compliant procurement has been introduced as a new paradigm in the construction industry to overcome those problems. However, the Malaysian construction industry has not fully adopted the concept of Shariah-compliant in construction procurement where the only infused parts are funding and insurance and there is a potential for the concept to be fully adopted as it is happening in various industries like banking, tourism and others. In spite of that, there is always a question whether the Shariah compliant can be fully embraced in the Malaysian construction industry. Therefore, a study to investigate the acceptability of the construction players on the concept of Shariah compliant procurement is carried out. The study is conducted by a combination of literature review and survey with the players in the construction industry. The outcome of the study indicates that construction players are going to accept the concept of Shariah compliant construction procurement though theirs understanding is at moderate level and some of them do not understand at all the concept.